The impact of leadership styles among UAE municipalities employees - Bakri, Mohammed Hariri; Mohammed Saeed Al Mazrouei, Abdulla Ali; Ismail, Albert Feisal @ Muhd Feisal; Md Razak, Mohamad Idham; De Mello, Geraldine (People and Global Business Association, 2023)
Purpose: This research examines the impact of four leadership behavior styles; directive, supportive, participative, and achievement-oriented. These four leadership behavior styles are retrieved from the Path goal theory, which considers the employee motivation determinants by the expectancy theory. Design/methodology/approach: The association between the leadership styles and behaviors suggested by the Path goal theory with employee motivation lacks the role of the entrepreneurial mindset factor, which stands on the thinking that enables the employee to overcome challenges, be decisive, and accept responsibility. This research tests the mediation effect of the entrepreneurial mindset factor to fill this gap and contributes significantly to the knowledge of leadership behavior styles. The study also validates the proposed conceptual framework using structural equations modeling, then uses smart PLS with the data collected from 341 employees from the UAE municipalities to test the constructed hypotheses of this research. Findings: The finding of this research revealed a positive and significant relationship between achievement-oriented style and employee motivation in the municipalities of the UAE, a positive and significant relationship between entrepreneurial mindset and employee motivation in the municipalities of the UAE, a positive and significant relationship between participative style and employee motivation in the municipalities of the UAE and positive and significant relationship between supportive style and employee motivation in the municipalities of the UAE. The mediation effect of the entrepreneurial mindset factor, there was a mediation of entrepreneurial mindset for the relationship between directive style and employee motivation. There is no mediation of entrepreneurial mindset for the relationship between achievement-oriented style and employee motivation, no mediation of entrepreneurial mindset for the relationship between participative style and employee motivation, and no mediation of entrepreneurial mindset for the relationship between supportive style and employee motivation. Research limitations/implications: The employees must be appreciated verbally or in writing for their activities in the municipalities to increase their powers and responsibilities and to provide training and career development opportunities. These are the primary leadership motivational factors that provide employees with psychological and social support rather than economic benefit. It can be stated that psycho-social motivation ties employees more. The findings can assist managers in determining which type of leadership style is most suitable in terms of outcomes, as well as how they can adjust their leadership styles to make them more successful and result-oriented. Originality/value: This research can be the first local empirical research to evaluate the organization's performance relationship between leadership behavior styles and the UAE municipality employees' motivation through an entrepreneurial mindset.